Pengaruh Pemberian Minuman Ringan Berkarbonasi terhadap Peningkatan Kadar Glukosa Darah dan Perubahan Diameter Pulau Langerhans Tikus Putih (Rattus norvegicus) Jantan Galur Sprague dawley - Firinda Soniya; Waluyo Rudiyanto (Medula, 2022)
The carbonated soft drinks consumption in this world have been increasing rapidly. Several of epidemiology studies have linked chronic consumption a carbonated soft drink with obesity, fatty liver disease, cardiovascular disease, metabolic syndrome, dental caries and osteoporosis. This research aims to determine the effect of carbonated soft drinks consumption to increase blood glucose levels and islets of Langerhans diameter changes rats in male Sprague dawley white rats (Rattus norvegicus). This research is a post test only control group design experimental study using 28 male white rats Sprague dawley which divided into 4 groups. K group only given an aquadest ad libitum 6 ml/200 gr/day, P1 group is given carbonated soft drinks 3 ml/200 gr/day, P2 group is given carbonated soft drinks 6 ml/200 gr/day and P3 group is given carbonated soft drinks 12 ml/200 gr/day for 30 days. The data of blood glucose levels was analysed by using One Way ANOVA test with result in p value=0.00 (p<0.05) then followed by Post Hoc LSD test with result in p value<0.05 for all of groups. The data of diameter Langerhans islets was analysed by using One Way ANOVA test with result in p value=0.394 (p>0.05). There is an effect of carbonated soft drinks consumption to increase blood glucose levels and there is no effect of carbonated soft drinks consumption to Langerhans islets diameter changes in Male Sprague dawley white rats (Rattus norvegicus) all 30 days long.